(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Mild or subclinical hypothyroidism may coexist with NephroticSyndrome (NS). But persistence of this hypothyroidism is related with remission ofproteinuria. Objectives of the study is to compare thyroid function status (FT4 andTSH) in the atypical and typical NS before and 4 weeks after steroid therapy. Materials and methods: This was a hospital based comparative observational studywith prospective follow up of study subjects. It was carried out in the Department ofPediatrics and in the Department of Nephrology, Chattogram Medical CollegeHospital (CMCH) Chattogram, Bangladesh from January to December’ 2017. A total83 diagnosed admitted cases of initial attack idiopathic NS, aged 1-18 years ofeither sex divided into 2 groups were included. Typically presented NS were in groupA and atypically presented NS were in group B. FT4 and TSH were estimated in allpatients on 2 occasions before and 4 weeks after initiation of steroid therapy andcomparison was done between 2 groups. Results: FT4 level was normal before and after steroid therapy in both typically andatypically presented nephrotic syndrome. Before steroid therapy, mean TSH valuewas found significantly raised in both groups (9.28±5.17 vs 7.26±3.67 μIU/ml).Proportion of subclinical hypothyroidism was statistically similar. After treatmentwith steroid, number of subclinical hypothyroid cases reduced in both groups withreduction of TSH value (3.13±1.14 vs 5.38±2.52 μIU/ml). But significant difference inTSH value was observed in between two groups. There was persistence of subclinicalhypothyroidism after treatment with steroid among 16.6 % (14.2% grade II and2.3% grade I) children with atypically presented NS and which is statisticallysignificant (p=0.006). Conclusion: Subclinical hypothyroidism persists in atypically presented nephroticsyndrome even after treatment with steroid. Chatt Maa Shi Hosp Med Coll J; Vol.19 (1); January 2020; Page 28-32